Identifying Consumer’s Needs of Health Information Technology through an Innovative Participatory Design Approach among English- and Spanish-speaking Urban Older Adults - Lucero, R.; Sheehan, B.; Yen, P.; Velez, O.; Nobile-Hernandez, D.; Tiase, V. (Applied Clinical Informatics, 2014)
Objectives: We describe an innovative community-centered participatory design approach, Consumer-centered Participatory Design (C2PD), and the results of applying C2PD to design and develop a web-based fall prevention system.Methods: We conducted focus groups and design sessions with English- and Spanish-speaking community-dwelling older adults. Focus group data were summarized and used to inform the context of the design sessions. Descriptive content analysis methods were used to develop categorical descriptions of design session informant’s needs related to information technology.Results: The C2PD approach enabled the assessment and identification of informant’s needs of health information technology (HIT) that informed the development of a falls prevention system. We learned that our informants needed a system that provides variation in functions/content; differentiates between actionable/non-actionable information/structures; and contains sensory cues that support wide-ranging and complex tasks in a varied, simple, and clear interface to facilitate self-management.Conclusions: The C2PD approach provides community-based organizations, academic researchers, and commercial entities with a systematic theoretically informed approach to develop HIT innovations. Our community-centered participatory design approach focuses on consumer’s technology needs while taking into account core public health functions.Citation: Lucero RJ, Sheehan B, Yen P-Y, Velez O, Nobile-Hernandez DL, Tiase VL. Identifying consumer’s needs of health hnformation technology through an innovative participatory design approach among English-and Spanish-speaking urban older adults. Appl Clin Inf 2014; 5: 943–957http://dx.doi.org/10.4338/ACI-2014-07-RA-0058
Keywords: Consumer health information; medical informatics; health information management; community-based participatory research; personal health records